Determining Factors of Fraud in Local Government - Sukhemi Sukhemi; Indah Ayu Arum Sari; Inayat Hanum Indriati (Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The objectives of this research are to analyze determining factors of fraud in local government. This study used internal control effectiveness, compliance with accounting rules, compensation compliance, and unethical behavior as an independent variable, while fraud as the dependent variable. The research was conducted at Bantul local government (OPD). The sample of this research were 86 respondents. The sample uses a purposive sampling method. The respondent data is analyzed with multiple linear regression. The results showed: Internal control effectiveness has an impact on fraud. Compliance with accounting rules does not affect fraud. Compensations compliance does not affect fraud. Unethical behavior has an impact on fraud.